The Effect of Teacher Professional Competence on Education Quality: A Literature Review - Hasan Hariri; Mohamad Thobi; Sowiyah Sowiyah; Riswandi Riswandi (Edumaspul: Jurnal Pendidikan, 2024)
Many aspects affect the quality education, one of which is the professional competence of teachers. Teacher competence is interesting topic to learn. This article aims to examine the effect of teacher professional competence on quality education. The articles used in this literature review were those obtained through Google Scholar by using the keywords teacher professional competence and quality oeducation. Based on the results of the literature review, the authors found that the professional competence of teachers has a positive and significant effect on the education quality. Keywords: teacher professional competence, quality education, literature review.